Evaluation of the clinical pharmacist services at a gynaecological oncology preadmission clinic - Natasha Triscari; Stephanie Wai Khuan Teoh; Marcus Femia (Elsevier, 2023)
Background: Pharmacists working in the multidisciplinary gynaecological oncology pre-admission clinic (PAC) are involved in the perioperative assessment of patients for a comprehensive medication history and information provision regarding withholding of medications before surgery. Objective: To evaluate the current services provided by pharmacists to multidisciplinary staff and patients attending the PAC. Methods: A staff and a patient feedback survey on the value and impact of PAC pharmacy services were distributed within the PAC. The impact of the PAC pharmacist was also assessed by analysing pharmacist interventions and key performance indicators documented. Results: Fifteen staff responses were recorded, 5 nursing staff, 2 midwives and 8 anaesthetists. Eighty-seven percent (n = 13) strongly agreed or agreed that pharmacists at PAC help reduce medication errors on admission. Staff strongly agreed 73% (n = 11) pharmacists obtain a more accurate medication history. Staff reported benefits in having a pharmacist at the clinic to discuss medication related questions with 87% (n = 13) strongly agreeing or agreeing with the statement. A staff overall satisfaction rating of 4.87 out of 5 was recorded. In the patient survey, respondents (n = 6) gave a 4.83 out of 5 rating in confidence in making changes to their medication and their overall satisfaction with the service provided. In reviewing data from January to June 2022, the number of patients seen by the pharmacist were 178 of 681 patients (26.1%) who attended the clinic. The most common medications involved in the pharmacist intervention include those that were advised to be withheld and those that required other changes to therapy prior to their procedure. Conclusion: The role of a PAC pharmacist can be greatly appreciated by the multidisciplinary team and patients. Pharmacist interventions and key performance indicators have demonstrated the important activities of clinical pharmacy services in the PAC in optimising patient care in medication management.